Gyroid‐Nanostructured All‐Solid Polymer Films Combining High H+ Conductivity with Low H2 Permeability. Issue 12 (7th May 2021) - Kobayashi, Tsubasa; Li, Ya‐xin; Hirota, Yuichiro; Maekawa, Asako; Nishiyama, Norikazu; Zeng, Xiang‐bing; Ichikawa, Takahiro
Abstract: Gyroid‐nanostructured all‐solid polymer films with exceedingly high proton conductivity and low H2 gas permeability have been created via crosslinking polymerization of mixtures of a zwitterionic amphiphilic monomer and a polymerizable imide‐type acid that co‐organize into bicontinuous cubic liquid‐crystalline phases. The gyroid nanostructures are visualized by reconstructing a 3D electron map from the synchrotron X‐ray diffraction patterns. These films exhibit high proton conductivity of the order of 10 −1 S cm −1 and extremely low H2 gas permeability of the order of 10 −15 mol m m −2 s −1 Pa −1 . These properties can be ascribed to the presence of the ionic liquid‐like layer along the gyroid minimal surface. Since these two characteristics are required for improving the performance of proton‐exchange membrane fuel cells, the present membrane design represents a promising strategy for the development of advanced devices, pertinent to establishing sustainable energy sources. Abstract : Gyroid‐nanostructured polymer films having multi‐layered H2 gas barriers and a 3D continuous proton conduction pathway have been created from specially‐designed bicontinuous cubic liquid‐crystalline monomers. They showed high proton conductivity of the order of 10 −1 S cm −1 and extremely low H2 gas permeability of the order of 10 −15 mol m m −2 s −1 Pa −1 .